2009 International Conference on Information and Communication Technologies 2009
DOI: 10.1109/icict.2009.5267189
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the effect of discrete attributes on the precision of classification methods

Abstract: Abstract:In this paper, the precision of logistic regression, naïve-Bayes and linear data classification methods, with regard to the Area Under Curve (AUC) metric have been compared. The effect of the parameters including size of the dataset, kind of the independent attributes, number of the discrete attributes and their values have been investigated. From the results, it can be concluded that in datasets consisting of both discrete and continuous attributes, the AUC of the three mentioned classifiers are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Therefore, it is possible to qualitatively model a series of continuous values if a label is assigned to them. Some studies [4] have shown that executing a prior process to discretize continuous features is more efficient than working directly with the continuous values. The discretization process reduces the computation memory usage and time in the application that develops classification algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible to qualitatively model a series of continuous values if a label is assigned to them. Some studies [4] have shown that executing a prior process to discretize continuous features is more efficient than working directly with the continuous values. The discretization process reduces the computation memory usage and time in the application that develops classification algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…GIS software is the core of the system for the implementation of the various operations of the GIS functionality, including data entry, data processing, database management, spatial analysis and graphical users' interface, which can be used as a platform for building geographic information application systems. Their representative products including ArcGIS, MapGIS, SuperGIS, GeoMedia, GeoStar and MapInfo [3][4] etc.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental investigation of the effect of discrete attributes on the precision of classification methods based on Area Under Curve (AUC) and found with increasing the number of the discrete attributes or with increasing the number of values in discrete attributes, the AUC of logistic regression is increased but linear classifier"s AUC decreases, and AUC of the naïve-Bayes classifier remains constant [6].…”
Section: Literature Surveymentioning
confidence: 99%